Pengaruh Current Ratio, Total Assets Turnover, Debt To Equity Ratio, dan Return On Equity Terhadap Harga Saham Pada Perusahaan Yang Terdaftar di JII Periode 2009-2013 - Puput Novitasari; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Islamic stocks in implementation are not contrary to the principles of sharia. Before investing their money investors should pay attention to advance the company's performance. One of its attention is fundamental analysis based on financial ratios. This research aims to analyze the effect of Current Ratio, Total Assets Turnover, Debt to Equity Ratio, and Return on Equity of stock price companies that listed on Jakarta Islamic Index in 2009-2013. The subject is the consistent companies listed on Jakarta Islamic Index during the research period. Selection method of the population is purposive sampling. Analysis method is multiple linear regression with significance level 0.05. The results indicate theese variables as a partially and simultaneuously insignificant influence on the stock prices. The value of coefficient determination 0.144 shows that 14.4% the stock prices is influenced by these variables, while for 85,6% are affected by other variables that are not included in this research.